2018
DOI: 10.1016/j.mtcomm.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Optical and chemical effects governing femtosecond laser-induced structure formation on polymer surfaces

Abstract: With the emergence of femtosecond technology, laser machining has recently led to the creation of novel porous structures on polymers. However, the mechanism behind their formation is yet to be understood. In this study, the dependence of femtosecond laser-induced surface structure on processing parameters is established at two distinct wavelengths (800 nm and 275 nm) for six different polymer films: LDPE, PC, PET, PLA, PMMA, and PTFE. All of the observed structures are then optically and chemically characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…The theoretical plausibility of this hypothesis on PMMA was also validated by the numerical simulations performed by Guay et al [20]. In our previous work, we further suggested that this phenomenon can occur on any polymer as long as its threshold fluence is large enough so that the melt layer is heated past Tc [12]. In summary, during femtosecond laser polymer ablation, energy delivery to the surface and subsequent boiling happens in the order of picoseconds [21].…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The theoretical plausibility of this hypothesis on PMMA was also validated by the numerical simulations performed by Guay et al [20]. In our previous work, we further suggested that this phenomenon can occur on any polymer as long as its threshold fluence is large enough so that the melt layer is heated past Tc [12]. In summary, during femtosecond laser polymer ablation, energy delivery to the surface and subsequent boiling happens in the order of picoseconds [21].…”
Section: Introductionsupporting
confidence: 62%
“…This phenomenon was initially observed on the side walls of inscribed lines and holes on poly(methyl methacrylate) (PMMA) and poly(carbonate) (PC) [10,11]. Since then, homogeneous polymer irradiation under certain conditions has been shown to cause the formation of a porous microstructure over the whole surface [7,12,13]. The resulting increase in surface area can be greatly beneficial for a number of applications such as omniphobic materials [13] or biomedical implants [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in a recent publication, Assaf et al have characterized the optical and chemical properties of polymer surfaces machined at two distinct wavelengths (λ = 800 nm and λ = 275 nm) (Assaf and Kietzig 2018). They have observed that polymer behavior depends on its cutoff wavelength λ c , below which the energy of a single photon is larger than the bandgap energy.…”
Section: Effect Of Wavelengthmentioning
confidence: 99%
“…Recently, there have been reports on femtosecond laser irradiation in which laser-induced periodic surface structures unique to polymers, for avoiding hydrophobicity, have been confirmed. 1,6,12 It is also known that ablation thresholds are reduced when irradiation with shorter pulse duration is used, regardless of the number of laser pulses to which the sample is exposed. 13,14 Data on the basic characteristics of femtosecond laser processing are required to form PLLA into three-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%